(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2021)
The technology has been growing from day to day in human life. The basic need of human to lead his/her life comfortably is a home. A home with updated latest technology which means a smart home. In such a scenario, there is a need to have an endeavour to have everything at the push of a button away, and more importantly, automated. Home Automation is such an endeavour, in which, all the electrical appliances present at home are connected to each other, having interactions with sensors placed at strategic positions in a closed loop manner to perform meagre tasks automatically, leaving less burden on the humans. With this project we are promoting the fact that Home Automation can greatly contribute to energy conservation too. This paper gives the basic idea use cisco packet tracer to implement smart home. Cisco implemented (IoT) functionalities in the latest version of the platform, and now it is possible to add all the smart devices, sensors, actuators, and devices, which simulate microcontrollers like Arduino or Raspberry Pi to the network. All IoT devices can be run on generic programs or modified by Java, Python or Blocky programming them. This makes Cisco Packet Tracer a perfect method to construct functional simulations for IoT.